2018
DOI: 10.1016/j.adolescence.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Early pubertal timing and adult adjustment outcomes: Persistence, attenuation, or accentuation?

Abstract: Early pubertal timing is associated with internalizing and externalizing problems during adolescence. However, few studies explicitly test whether early puberty is especially problematic for those with pre-existing problems (i.e., accentuation) and little is known about whether the negative correlates of early pubertal timing persist past young adulthood. We address these questions using longitudinal data from up to 451 participants in the Iowa Youth and Families project (e.g., Ge, Conger, & Elder, 1996, 2001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 44 publications
6
29
0
Order By: Relevance
“…The accentuation hypothesis predicts that maladaptive behaviors are thought to become magnified by early puberty, compared to later maturing peers. In line with these considerations, current research shows that early pubertal timing amplifies the link between childhood problems and adolescent substance use (Beltz, Corley, Wadsworth, DiLalla, & Berenbaum, 2019;Senia, Donnellan, & Neppl, 2018). Effects may not persist into adulthood, however (Senia et al, 2018).…”
Section: Theory Strand 1: Early Puberty Amplifies Pre-existing Problemssupporting
confidence: 58%
See 1 more Smart Citation
“…The accentuation hypothesis predicts that maladaptive behaviors are thought to become magnified by early puberty, compared to later maturing peers. In line with these considerations, current research shows that early pubertal timing amplifies the link between childhood problems and adolescent substance use (Beltz, Corley, Wadsworth, DiLalla, & Berenbaum, 2019;Senia, Donnellan, & Neppl, 2018). Effects may not persist into adulthood, however (Senia et al, 2018).…”
Section: Theory Strand 1: Early Puberty Amplifies Pre-existing Problemssupporting
confidence: 58%
“…In line with these considerations, current research shows that early pubertal timing amplifies the link between childhood problems and adolescent substance use (Beltz, Corley, Wadsworth, DiLalla, & Berenbaum, 2019;Senia, Donnellan, & Neppl, 2018). Effects may not persist into adulthood, however (Senia et al, 2018). Presently, there is little evidence for this hypothesis for cognitive outcomes.…”
Section: Theory Strand 1: Early Puberty Amplifies Pre-existing Problemsmentioning
confidence: 79%
“…It is presently unclear whether pubertal timing predicts the onset of depressive episodes in boys, especially as many of the seminal studies of pubertal timing as a risk factor for depression disorders did not include boys. Additionally, foundational work operationalized pubertal timing as age at menarche or using categorical variables of pubertal timing (which is not current best practice: Senia, Donnellan, & Neppl, 2018; Smith‐Woolley, Rimfeld, & Plomin, 2007; Toffol et al, 2014). A small meta‐analysis reported that evidence supports early pubertal timing as a risk factor for the onset of depression in girls, but more studies of high quality are needed as the overall quality of the evidence was low (Galvao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies investigate the persistence of associations into adulthood. In those that do, the associations appear to attenuate in later adolescence and early adulthood (Joinson et al ., 2013; Senia et al ., 2018), though there is some evidence for persistent effects (Stattin and Magnusson, 1990; Copeland et al ., 2010; Lien et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%